2011
DOI: 10.1136/annrheumdis-2011-200421
|View full text |Cite
|
Sign up to set email alerts
|

The ACPA recognition profile and subgrouping of ACPA-positive RA patients

Abstract: These data show that the ACPA response is highly diverse with respect to recognition of specific citrullinated epitopes. Furthermore, the authors' data indicate that clinical correlates in established ACPA-positive RA are independent from the specific (group of) citrullinated peptides recognised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 42 publications
(44 reference statements)
5
53
1
1
Order By: Relevance
“…25,26,30,32,33 The fact that considerable cross-reactivity between ACPA recognizing different antigens within a single patient exists, notably complicates identification of ''true'' antigenic structures and the involvement of citrullinated antigens in the pathophysiology of RA, as extensive characterization of ACPA responses to a single antigen might be a proxy for recognition of other citrullinated antigens. Despite the pronounced cross-reactivity prevailing in these ACPA responses, our results and current knowledge indicate that only limited side chain-specific reactivity in combination with backbone interactions is necessary to obtain reactivity with these antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26,30,32,33 The fact that considerable cross-reactivity between ACPA recognizing different antigens within a single patient exists, notably complicates identification of ''true'' antigenic structures and the involvement of citrullinated antigens in the pathophysiology of RA, as extensive characterization of ACPA responses to a single antigen might be a proxy for recognition of other citrullinated antigens. Despite the pronounced cross-reactivity prevailing in these ACPA responses, our results and current knowledge indicate that only limited side chain-specific reactivity in combination with backbone interactions is necessary to obtain reactivity with these antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Most important, these results indicated that ACPA responses against several citrullinated autoantigens coexist in RA patients, 31 which is in accordance to studies describing that ACPApositive RA patient sera recognize a number of citrullinated antigen binding regions, indicating crossreactive ACPA responses. 32 Additional analyses of ACPA responses to citrullinated proteins have confirmed that ACPA indeed are cross-reactive, but apparently this cross-reactivity is not complete, as distinct noncross-reactive ACPA responses have been detected as well. 25,33 This cross-reactivity, prevailing in the majority of ACPA responses, identifying multiple citrullinated targets, complicates the identification of the antigen(s) responsible for the initiation of the ACPA response.…”
Section: Introductionmentioning
confidence: 97%
“…In RA, one of the genetic risk HLA alleles, HLA-DRB1*0401, has recently been associated with presentation of citrullinated peptides, allowing for activation of citrulline-specific T cells (22). These T cells may is substituted for arginine (34,35). Most of these antigenic citrullinated antigens are extracellular proteins, although intracellular citrullinated proteins have also been identified as targets of ACPAs.…”
Section: T Cell Help For Autoantibody Productionmentioning
confidence: 99%
“…Although ACPA can be detected many years before the onset of symptoms of RA,21 22 emerging data indicate that it is unlikely that predictive algorithms on the basis of the recognition of specific citrullinated epitopes will be helpful, as studies performed in different populations revealed that parallel to a rise in the ACPA titre no specific reactivity could be identified that associated with the precipitation of disease 23–25. Likewise, clustering of these reactivities does not seem to provide additional information regarding the clinical phenotype of RA, for example, with respect to the disease activity score, swollen or tender joint counts26 27 or regarding the prediction of disease evolution in the pre-RA stage such as is present in patients with ACPA-positive arthralgia 24. Also, current data do not indicate added value of ACPA fine specificity testing in the prediction of radiological progression in the RA population.…”
Section: Maturation Of the Acpa Responsementioning
confidence: 69%